Mapping the underworld: integrated GNSS based positioning and GIS based GNSS simulation - Taha, Ahmad Adnan Mohammad (2008)
The United Kingdom utility services are facing the challenge of "mapping the underworld" over four million kilometres of buried pipes and cables (a combination of water, sewage, gas, electricity and drainage). Having accurately mapped pipes and cables increases the efficiency of street works projects, but many existing pipes and cables were only mapped relative to other topographic map features and to varying levels of accuracy.